PELAKSANAAN PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DI SATUAN NARKOTIKA POLRES BUKITTINGGI - Failin Alin (STIH Putri Maharaja, 2020)
Drugs, on one hand are materials used in the field of medicine, health service and the development of science that on the other hand can also affects a detrimental dependency if misused or used without control and supervision. After the enactment of Law Number 35 Year 2009 Concerning Narcotics, all actions that export, import, produce, plant, store, distribute and / or use narcotics and their sanctions are regulated therein which aims to tackle and eradicate these criminal acts. The use of narcotics without strict and thorough control and supervision is very detrimental and constitutes a huge danger to the lives of people, the community, the nation, and the State as well as Indonesia's national security. When seen in Bukittinggi Police Station from year to year the number of narcotics offenders increased and overall the case documents already complete (P21). The investigation of narcotics crime in Bukittinggi Police has been running according to the rules, which is based on the Criminal Procedural Law, however the implementation has not been effective because there are remain obstacles in the implementation of investigation.